Competencies of Pricipals of Private Early Childhood Educational Institutions and their Importance: Stakeholder Opinion Analysis - Pečiulienė, Lina (Jaunųjų mokslininkų darbai, 2019)
Since the management of private early childhood educational institutions has not been sufficiently studied, there is no clear opinion what competencies key stakeholders would like to see in the principals of these institutions and how required competencies should be assessed.Empirical research was carried out to compare opinions of key stakeholders (founders, principals, employees, parents (present and potential customers)) in a theoretical model of principals’ competencies.The ranking of principal’s competencies in the generalized model showed that the most desirable group of competencies is the ability to build trust.
Keywords: private early childhood educational institution; stakeholder management; model of principal’s competencies